Medial lingual lymph node metastasis in carcinoma of the tongue. Issue 1 (February 2020) - Eguchi, Kohtaro; Kawai, Shigeo; Mukai, Masayoshi; Nagashima, Hiroaki; Shirakura, Satoshi; Sugimoto, Taro; Asakage, Takahiro
Abstract: Lingual lymph node metastases are rarely seen in carcinoma of the tongue, and these nodes are not removed during neck dissection. Lingual lymph nodes are classified into medial and lateral groups, and metastasis to the former is extremely rare. A 55-year-old male with squamous cell carcinoma of the tongue, (stage T4aN0M0), underwent hemiglossectomy with neck dissection and free flap reconstruction. The lingual septum had a mass, 8 mm in size, which was diagnosed as medial lingual lymph node metastasis on histopathology. The patient developed multiple distant metastases and died of disease 18 months after the initial surgery. The presence of medial lymph node metastasis could result in contralateral neck metastases and worsen prognosis. Such cases may warrant more intensive therapy than recommended by current guidelines.